Zdravljenje vedenjskih in psihičnih simptomov demence z metodami neinvazivne možganske stimulacije - Plaznik Šporin, Blaž (Medicinski razgledi, 2023)
Due to its high prevalence, dementia represents a big public health problem and because of the ageing population it is expected that the number of patients will continue to rise. Dementia is commonly associated with behavioural and psychological symptoms of dementia, which signify a worse prognosis, challenges in caring for these patients and a worse quality of life. Due to the resistance of behavioural and psychological symptoms of dementia to pharmacological treatment, there is an increased interest in their non-pharmacological management, including different methods of non-invasive brain sti mulation. These have effect by modulating the synaptic activity of the neurons and cortical excitability with electric current or magnetic pulses. These methods are safe with mild and transient side effects. The efficacy and safety of non-invasive brain stimulation in the treatment of behavioural and psychological symptoms of dementia were confirmed in several clinical studies, with repetitive transcranial magnetic stimulation being the most successful, according to studies published so far. In this article, the review of literature and results of these studies are presented.
Keywords: demenca; neinvazivna možganska stimulacija; spreminjanje vzdržnosti možganske skorje; vedenjski in psihični simptomi demence